Mechanochemical Treatment for the Extraction of Lithium from Hard Rock Minerals: A Comprehensive Review - Yuik Eom; Laurence Dyer; Aleksandar N. Nikoloski; Richard Diaz Alorro (Metals)
Lithium (Li) extraction from Li hard rock minerals involves thermal activation at elevated temperatures and the use of corrosive reagents. The reagents can damage the environment if they are not adequately contained as part of the process, and the high temperatures require large amounts of energy, which can contribute to greenhouse gas emissions unless renewable energy sources are used. These concerns have motivated research into many alternative methods to partially or completely replace the conventional process while maintaining or enhancing the Li extraction rate. Mechanochemistry is one of these alternative methods, as it has the potential to increase the reactivity of Li resources with reagents while reducing the need for corrosive reagents. Mechanochemistry has been applied to mineral processing, particularly introduced as the pre-treatment method before pyro- or hydrometallurgical processes, for several decades. In recent years, a few studies about direct Li extraction from mechanochemically activated hard rock minerals utilizing various co-grinding additives have been reported. This review deals with the application of mechanochemistry to process the Li-bearing hard rock minerals, spodumene and lepidolite, and the mechanisms of the mechanochemical treatment.